Impact of microaxillar mechanical left ventricular support on renal resistive index in patients with cardiogenic shock after myocardial infarction: a pilot trial to predict renal organ dysfunction in cardiogenic shock. Issue 2 (March 2020) - Markus, Birgit; Patsalis, Nikolaos; Chatzis, Georgios; Luesebrink, Ulrich; Ahrens, Holger; Schieffer, Bernhard; Karatolios, Konstantinos
Objectives: To evaluate the effects of left ventricular support with the microaxial left ventricular pump using the Impella device on the renal resistive index assessed by Doppler ultrasonography in haemodynamically stable patients with cardiogenic shock following myocardial infarction. Methods: A non-randomised interventional single-centre study. Consecutive patients with cardiogenic shock supported with an Impella were included during May 2018 and October 2018. The renal resistive index determined as a quotient of (peak systolic velocity – end diastolic velocity)/ peak systolic velocity was obtained using Doppler ultrasound; invasive blood pressure was determined in radial artery simultaneously for safety reasons. Results: A total of 15 patients were measured. The renal resistive index was determined in both kidneys in 13 patients and for one kidney in two patients, respectively. The mean difference between right and left renal resistive index was 0.026 ± 0.023 ( P =0.72). When increasing the Impella microaxillar mechanical support by a mean of 0.44 L/min (±0.2 L/min), the renal resistive index decreased significantly from 0.66 ± 0.08 to 0.62 ± 0.06 ( P <0.001) consistently in all patients, whereas systolic or diastolic blood pressure remained unchanged. Conclusions: Microaxillar mechanical support by the Impella device in haemodynamically stable patients with cardiogenic shock led to a significant reduction of the renal resistive index without affecting systolic or diastolic blood pressure. This observation is consistent with the notion that Impella support may promote renal organ protection by enhancing renal perfusion.